Colon cancer surgery. Five years of experience. - Nicolás Rubio Silveira; Javier López Mayedo; Carlos Echevarría del Risco; Katia García Paneca (Medisur)
Fundament: Colon-rectal cancer is one of the most frequent neoplams in eastern countries and it is the second most frequent type of cancer just behind cancer of the lungs and of the breast respectively. In spite of the advances in the last few years in regards to treatment, colon cancer is the most frequent cause of death due to cancer. Objective: To know morbimortality due to cancer of the colon after both, surgery and oncological treatment. Method: Descriptive - retrospective sdtudy carried out at the Military hospital ¨Dr. Octavio de la Concepción y de la Pedraja¨ from Camaguey Province from January 1999 to January 2004.The sample was composed by 20 patients operated of well differentiated adenocarcinoma of the colon. The variables under study were: Age, Sex, place, anatomical localization of the tumor, anatomoclinical stage according to Dukes classification, evidencies of far metastases, type of surgery type of oncologic treatment. Results: There was a predominance of males (55%) aged more than 45 years old. 55% of the tumors were located in the sigmoid colon. There was a resect of the tumor in 16 cases and only 2 have died due to the disease . Chemotherapy with 5 fluoruracile was applied to 9 patients, with good results.